Commitment to what is Necessary As an Idea to Embody the Element of Morality in Law - Alahmed, Mohammed; Smael, Tahsin (Journal of Legal Sciences, 2023)
Some actions do not come from the law, but rather from the moral will of a person, and these actions are necessary for people to do because a person is a moral being whose existence is determined by his relationship with values. And, since ethics is one of the normative sciences that link the end to the means, that is, of a person study is not limited to what is an object, or a current situation, but it should be. Therefore, task of a person is to set conditions that must be met in human will and actions in order to become the subject of legal and ethical rulings. This is because there is a close relationship between law and morality, and despite the absence of a legal rule that obliges individuals to do actions, such as extending a hand and helping others, or directing someone to a hospital, however, there is a benevolent will besides the duty that people must perform as a pillar of morality and compliance with the moral law. As long as the ethical behavior includes the necessity of adhering to the duty, and in the event of a violation of the moral imperative, it has violated the moral responsibility. This is because the moral duty imposes on a person two duties: a positive duty through helping others and the breadth of others, and a negative duty imposed by not assaulting others. Besides that the person who adheres to the first duty obtains an honorable non-financial moral reward, always longer, influenced and more, and strengthens his behavior and obtains satisfaction in himself, but if he does not he adheres to the second duty because he deserves to receive appropriate punishment. Nevertheless, although this moral imperative does not include any of the technical or tactical legal standards, it is characterized by the capacity of specialization and obligation when a person feels when he expresses his willingness to help others, so it immediately becomes a binding rule despite its lack of codification and retention of its noble value, and has committed itself to what is it is necessary, so it is not necessary to codify these fine and wonderful ethics.